Comparison of bretschneider HTK and blood cardioplegia (4:1): A prospective randomized study - AK, KORAY; KARARMAZ, ALPER; ARSAN, SİNAN (My University, 2023)
Background We compared the effect of intermittent blood and histidine-tryptophan-ketoglutarate (HTK) solution of Bretschneider on myocardial histopathology and perioperative outcome. Methods Forty adult cardiac surgery patients were grouped into two (n = 20 for each): (1) Intermittent blood cardioplegia (IBC): had repeated cold 4:1 blood cardioplegia and (2) HTK: had a single dose of cold HTK for cardioprotection. Creatine kinase (CK)-MB, Troponin-I (cTn-I), pH, and lactate were studied in coronary sinus blood before and after aortic cross-clamping (AXC) and systemic blood at postoperative 6th, 24th, and 48thhours. Myocardial biopsy was performed before and after AXC for light microscopy. Vacuolation, inflammation, edema, and glycogen were graded semiquantitatively (from 0 to 3). The myocardial apoptotic index was evaluated via the terminal deoxynucleotidyl transferase dUTP nick end labeling. Results There were no differences in perioperative clinical outcomes between the groups. The coronary sinus samples after AXC were more acidotic (7.15 ± 0.14 vs. 7.32 ± 0.07, p = 0.001) and revealed higher CK-MB (21.0 ± 12.81 vs. 12.60 ± 11.80, p = 0.008) in HTK compared with IBC. The HTK had significantly a higher amount of erythrocyte suspension intraoperatively compared with IBC (0.21 ± 0.53 vs. 1.68 ± 0.93 U, p = 0.001). Microscopically, myocardial edema was more pronounced in HTK compared with IBC after AXC (2.25 ± 0.91 vs. 1.50 ± 0.04, p = 0.013). While a significant increase in the apoptotic index was seen after AXC in both groups (p = 0.001), no difference was detected between the groups (p = 0.417). Conclusion IBC and HTK have a similar clinical outcome and protective effect, except for more pronounced myocardial edema and increased need for intraoperative transfusion with HTK.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Kardiyoloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Cardiovascular; Surgery Medicine Sciences; Health Sciences; Klinik Tıp (MED); Klinik Tıp; CERRAHİ; SOLUNUM SİSTEMİ; KALP VE KALP DAMAR SİSTEMLERİ; Clinical Medicine (MED); CLINICAL MEDICINE; SURGERY; RESPIRATORY SYSTEM; CARDIAC & CARDIOVASCULAR SYSTEMS; Cerrahi; Akciğer ve Solunum Tıbbı; Kardiyoloji ve Kardiyovasküler Tıp; Surgery; Pulmonary and Respiratory Medicine; Cardiology and Cardiovascular Medicine; cardiac; histopathology; ischemia; myocardial protection